THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS AT CAFÉ NOKA IN SUNGAI PENUH CITY - Ditama, Rezki Agrisa; Azhar, Azhar; Nilda, Elvi; Syamsarina; Desiana; Mailindra, Wiyan (Asian Journal of Islamic Economic Studies, 2025)
This study aims to analyze the influence of brand image and product quality on purchasing decisions at Café Noka in Sungai Penuh City. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to Café Noka customers and analyzed using multiple linear regression techniques. The results show that brand image and product quality have a positive and significant impact on purchasing decisions. A strong brand image enhances customer trust, while good product quality contributes to customer satisfaction, ultimately encouraging purchasing decisions. The findings suggest that Café Noka should maintain and improve its brand image and product quality to increase customer loyalty and purchase interest.